Integrated management of marketing risk and efficiency - Rutkauskas, Aleksandras Vytautas; Ginevičius, Adomas (Journal of Business Economics and Management, 2011)
There are two principal problems arising for marketing management: first—the increase of marketing ability to use effectively its resources, and second—to inventory the risks influencing marketing activity in order to develop their management strategy. Considering exceptional riskiness of marketing, the solution of marketing efficiency problems is not separable from identification of risks, influencing marketing, and their management strategies development. Integrated analysis of marketing efficiency and risk management problems is performed in two ways. First, a marketing risks portfolio management situation is analysed in such a way that resources, intended for risk management, are distributed among the means of decreasing value at risk in such a manner that the overall value of risk, i.e. the resultant of all risk values, would be minimal. Second, based on the expert efficiency estimates for a unit of costs in every element of marketing structure, a distribution of costs is pursued which would uphold the best increase of marketinggenerated marginal utility. To find the solution, imitative modeling and stochastic optimization methods are used.Article in English.Integruotas marketingo rizikos ir efektyvumo valdymasSantrauka. Kyla dvi pagrindines marketingo valdymo problemos: pirma—tai marketingo gebejimo efektyviai naudoti jam skirtus išteklius didinimas, antra—inventorizuoti marketingo veiklai itak daranèias rizikas, siekiant parengti ju valdymo strategij. Atsižvelgiant i išskirtini marketingo rizikingum, jo efektyvumo problemu sprendimas neatsiejamas nuo riziku, daranèiu poveiki marketingui, identifikavimo ir ju valdymo strategiju sukurimo. Straipsnyje marketingo efektyvumas ir rizikos valdymo problemos nagrinejamos dviem budais. Pirmas—nagrinejama marketingo riziku portfelio valdymo situacija, kai ištekliai, skirti rizikai valdyti, dalijami tarp priemoniu, skirtu riziku vertei mažinti (Value at Risk), taip, kad bendroji rizikos verte, t. y. visu rizikos verèiu atstojamoji, butu minimali. Antras—remiantis ekspertu efektyvumo iverèiais snaudu vienetui kiekviename marketingo strukturos elemente, ieškomas toks snaudu padalijimas, kuris puoseletu naudingiausi marketingo sukuriamo ribinio naudingumo prieaugi. Sprendimams rasti pasitelkti imitacinio modeliavimo ir stochastinio optimizavimo metodai.Reikšminiai žodžiai: marketingo efektyvumas, marketingo rizika, integruotas marketingo efektyvumo ir rizikos valdymas.